MANAGEMENT OF WATER SUPPLY TO KASOA COMMUNITY IN GHANA - YAMOAH, ISAAC (My University, 2012)
The Ghana government introduction of the weija dam water supply programme to the Accra Metropolis is faced with the problem of inability to expand the treatment plant and in particular, water supply to Kasoa community. This research study focused on the Kasoa district as a case study and examines underlying reasons that contribute to the problem of inadequate water supply to the district. In order to understand technical and social dynamics around the problem of scarce water supply in the Kasoa district, the research focused on the water meter distribution system which forms part of the water supply implementation strategy. The research fundamentally used qualitative methodology with Kasoa district as the case study for collect of in-depth information from informants. Quantitative tools are used in data presentation and analysis. The purpose of this research was to investigate the problem of inadequate water supply to Kasoa community and develop how the meter system could be improved. The research shows that the water supply programme initiative has been fairly successful in the kasoa district. However , incidence of corruption in the form of selling water meters hinder the programme from achieving its objective of ensuring water gets to every home in the community as evidenced by some pockets of hungry community district managers and water billing officials in the district. Corruption is mainly caused by lack of accountability measures in the design of the implementation strategy and lack of empowerment of communities to demand accountability from authorities
MM thesis - P&DM
Keywords: Water supply, Ghana